Arctic fox dispersal from Svalbard to Canada: one female’s long run across sea ice - Fuglei, Eva; Tarroux, Arnaud (Polar research, 2019)
We report the first satellite tracking of natal dispersal by an Arctic fox (Vulpes lagopus) between continents and High-Arctic ecosystems. A young female left Spitsbergen (Svalbard Archipelago, Norway) on 26 March 2018 and reached Ellesmere Island, Nunavut, Canada, 76 days later, after travelling a cumulative distance of 3506 km, bringing her ca. 1789 km away (straight-line distance) from her natal area. The total cumulative distance travelled during the entire tracking period, starting when she left her natal area on 1 March 2018 and ending when she settled on Ellesmere Island on 1 July 2018, was 4415 km. This is among the longest dispersal events ever recorded for an Arctic fox. Crossing extensive stretches of sea ice and glaciers, the female moved at an average rate of 46.3 km/day ± 41.1 SD. The maximum movement rate was 155 km/day and occurred on the ice sheet in northern Greenland. This is the fastest movement rate recorded for this species. The northernmost location recorded was on the sea ice off northern Greenland at a latitude of 84.7°N. The Arctic fox was of the blue colour morph typical for coastal environments, where Arctic foxes are adapted to food webs without lemmings but with substantial inputs of marine food resources. The Arctic fox settled on Ellesmere Island in a food web with lemmings, thereby switching ecosystems. Our observation supports evidence of gene flow across Arctic regions, including those seasonally bridged by sea ice, found in studies of the circumpolar genetic structure of Arctic fox populations. View the supplementary animation. This article has a related Erratum.